Efficiency enhancement of novel ITO/ZnSe/CNTs thin film solar cell - A. Bakour; M. Al-Hattab; O. Bajjou; K. Rahmani (Chemical Physics Impact, 2024)
This study presents a novel photovoltaic cell design utilizing a layered structure of Indium Tin Oxide (ITO), Zinc Selenide (ZnSe), and Carbon Nanotubes (CNTs) for enhanced solar energy conversion. We employed the Solar Cell Capacity Simulator (SCAPS-1D) to model and optimize the device under AM 1.5 spectrum conditions. Our simulations systematically investigated the influence of key parameters including layer thicknesses, doping concentrations, temperature, back contact work function, and parasitic resistances on cell performance. The optimized structure demonstrated a theoretical power conversion efficiency of 29.91%, with an open-circuit voltage (Voc) of 799 mV, a short-circuit current density (Jsc) of 43.49 mA/cm², and a fill factor (FF) of 86.02%. These promising results are attributed to the synergistic combination of CNTs' broad spectral absorption, ZnSe's effective charge separation, and optimized layer properties. We found that the CNT absorber layer's doping concentration significantly impacted cell performance, with an optimal value of 10¹⁷ cm⁻³. The ZnSe buffer layer thickness showed minimal effect on efficiency within the studied range. Temperature increases from 300 K to 400 K led to a significant efficiency drop from 33.97% to 24.65%, primarily due to Voc reduction. While these results represent idealized conditions and upper theoretical limits, they provide valuable insights for the potential of CNT-based solar cells. This study offers a roadmap for future experimental work in high-efficiency thin-film photovoltaics, highlighting the promise of novel material combinations and the importance of device architecture optimization.